Post Operative Delirium (POD) in Surgical Patients at PMCH Nawabshah - Zulficiar lmtiaz Memon, Abdul Hakeem Jamali, Ubaidullah Shaikh, Inayat Ali Zardari, Mashooq Ali Khawaja, Altaf Hussain Ghumro , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the prevalence of postoperative delirium in surgical patients. Methods: A cross-sectional study conducted in surgical department of Peoples Medical College Hospital and Surgical Intensive Care Unit (SICU), on 90 patients in 3 years from May 2013 to April 2016. Patients presented with features of unaware to surroundings, diminished memory, not fully oriented by time, place and person, unable to name objects, write or present with rambling speech and perceptional disturbances. These were treated conservatively by seeking help from psychiatrist also. Results: In total 90 patients in three years of 60 years developed this disease after emergency surgical procedures and their complications where as only 30 patients were of elective list. Females were more commonly affected as compared to males, Old age patients were the common victims. 30 (50%) patients out of 60 emergency cases developed the disease due to fecal fistula and stoma formation. 12 (40%) patients of elective list developed the disease due to infected wound after Onlay and Sublay mesh repair. Conclusion: Medical treatment is the best choice with help of psychiatrist. Preoperative assessment by anesthetist is must to rule out its risk factors like dementia etc.